2019
DOI: 10.1021/acsami.9b04535
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Superheated Steam Generation for Portable Sterilization under Ambient Pressure and Low Solar Flux

Abstract: Superheated solar steam generation above 100 °C is critical for many important applications such as sterilization but is challenging to achieve under natural fluctuating low-flux solar illumination and often requires pressurization and the usage of expensive optical concentrators. Herein, we demonstrate generation of superheated steam under ambient pressure and low-flux solar illumination by integrating a recently emerged interfacial evaporation design into a solar vacuum tube. Within the tube, the water vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 54 publications
2
63
0
Order By: Relevance
“…12,15,19,31,33,[49][50][51][52][53][54][55] A few recent studies employed a subsequent superheating stage to boost the steam temperature beyond 100 C in open systems (open symbols in quadrant II). 20,32,48 This work demonstrates that it is possible to generate saturated and pressurized steam with low optical concentration represented by the only filled symbol in quadrant II.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…12,15,19,31,33,[49][50][51][52][53][54][55] A few recent studies employed a subsequent superheating stage to boost the steam temperature beyond 100 C in open systems (open symbols in quadrant II). 20,32,48 This work demonstrates that it is possible to generate saturated and pressurized steam with low optical concentration represented by the only filled symbol in quadrant II.…”
Section: Methodsmentioning
confidence: 76%
“…A few studies have shown the possibility to further boost the steam temperature via a subsequent superheating stage (open symbols in quadrant II). 20,32,48 However, due to the relatively low efficiency, a pressurized saturated steam generation beyond 100 C was only available in quadrant I in previous research. Enabled by the highly efficient thermal concentration approach, this work provides a viable solution for generating saturated and pressurized steam-represented by the filled star in quadrant II.…”
Section: Discussionmentioning
confidence: 99%
“…The Escherichia coli bacteria were used as the indicator in the steam sterilization experiments. 46 The sterile tubes containing the bacterial solution were exposed to hot steam within the sanitizer for 15 min under a heating power density of 18 kW/m 2 (Figure S8). Figure 5d presents that all the E. coli bacterial cells were killed by the LIEH-based steam sanitizer, but many bacteria cells were still alive after treatment in the BEH-based steam sanitizer due to the low vapor temperature.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the heat carried by hot water vapor can be recycled for electricity generation via thermoelectric ( Figure a) and thermomechanical effects (Figure 15b), [ 66,83 ] or directly utilized for rapid sterilization. [ 81,150–152 ] Converting downward heat loss into electricity has also been demonstrated through thermoelectric method as shown in Figure 15c, which is achieved by taking the advantage of inherently established temperature difference between hot solar absorber and cool water body. [ 68,79,85 ]…”
Section: Perspectivesmentioning
confidence: 99%